Influence of Contamination with Inorganic Impurities on the Durability of a 1 kW DMFC System. Issue 1 (6th December 2013) - Kimiaie, N.; Trappmann, C.; Janßen, H.; Hehemann, M.; Echsler, H.; Müller, M.
Abstract IEK‐3 at Forschungszentrum Jülich successfully replaced the battery tray of a horizontal order picker (ECE 220, Jungheinrich) with a direct methanol fuel cell (DMFC) hybrid system in the kilowatt class. The DMFC combined with a lithium‐ion battery forms the hybrid drive for electrically driven horizontal order pickers. Such vehicles are used to transport and collect goods for orders in warehouses. The order picker is fueled by pure methanol to achieve a maximum range with the smallest possible space for the battery tray. An advantage of such energy systems is that there is no need for the relatively complicated and time‐consuming recharging of the conventional lead‐acid batteries, nor are spare batteries required for multishift operation. This study focuses on the influence of contamination with inorganic impurities on the durability of the 1 kW DMFC system V3.3‐1. The data from a long‐term test will be presented, in which the DMFC system was subjected to a realistic dynamic load profile for 3, 000 h. The impurities identified in the post‐mortem analysis of the membrane electrode assembly will be outlined as well the influence of selected impurities, the sources of these impurities and how the DMFC V3.3‐2 system was modified on the basis of these findings.